Target Zones in History and Theory: Lessons from an Austro-Hungarian Experiment (1896-1914) - Marc Flandreau; John Komlos (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
The first known experiment with an exchange rate band took place in Austria- Hungary between 1896 and 1914. The rationale for introducing this policy rested on precisely those intuitions that the modern literature has emphasized: the band was designed to secure both exchange rate stability and monetary policy autonomy. However, unlike more recent experiences, such as the ERM, this policy was not undermined by credibility problems. The episode provides an ideal testing ground for some important ideas in modern macroeconomics: specifically, can formal rules, when faithfully adhered to, provide policy makers with some advantages such as short term autonomy? First, we find that a credible band has a “microeconomic” influence on exchange rate stability. By reducing uncertainty, a credible fluctuation band improves the quality of expectations, a channel that has been neglected in the modern literature. Second, we show that the standard test of the basic target zone model is flawed and develop an alternative methodology. We believe that these findings shed a new light on the economics of exchange rate bands.
urn:nbn:de:bvb:19-epub-75-1
Keywords: F31; N32; 330; target zones; credibility; exchange rate stability; monetary policy autonomy